Reconstructing ecosystem functions of the active microbial community of the Baltic Sea oxygen depleted sediments - Petter Thureborn; Andrea Franzetti; Daniel Lundin; Sara Sjöling (PeerJ, 2016)
Baltic Sea deep water and sediments hold one of the largest anthropogenically induced hypoxic areas in the world. High nutrient input and low water exchange result in eutrophication and oxygen depletion below the halocline. As a consequence at Landsort Deep, the deepest point of the Baltic Sea, anoxia in the sediments has been a persistent condition over the past decades. Given that microbial communities are drivers of essential ecosystem functions we investigated the microbial community metabolisms and functions of oxygen depleted Landsort Deep sediments by metatranscriptomics. Results show substantial expression of genes involved in protein metabolism demonstrating that the Landsort Deep sediment microbial community is active. Identified expressed gene suites of metabolic pathways with importance for carbon transformation including fermentation, dissimilatory sulphate reduction and methanogenesis were identified. The presence of transcripts for these metabolic processes suggests a potential for heterotrophic-autotrophic community synergism and indicates active mineralisation of the organic matter deposited at the sediment as a consequence of the eutrophication process. Furthermore, cyanobacteria, probably deposited from the water column, are transcriptionally active in the anoxic sediment at this depth. Results also reveal high abundance of transcripts encoding integron integrases. These results provide insight into the activity of the microbial community of the anoxic sediment at the deepest point of the Baltic Sea and its possible role in ecosystem functioning.